Strategi Pemasaran Perlengkapan Haji dan Umrah di Kota Padang - Lara Paradilla; Sandra Dewi (Universitas 45 Surabaya, 2024)
This research is motivated by the lack of resources at PT Arminareka Perdana which hinders the implementation of the plan set, the number of competitors with PT Arminareka Perdana, the lack of marketing because it only promotes through social media. The objectives of this study are: 1). the lack of human resources at PT Arminareka Perdana in Padang city hinders the implementation of the plan that has been set and affects the quality of the services provided. 2). There are still many competitors with PT Arminareka Perdana in Padang city. 3). Only promoting through social media only, this makes its marketing not known to everyone. This research method uses descriptive qualitative research methods, where the data collection techniques are through interviews, observation, and documentation. Then the research uses the SWOT Analysis method. And as for the results of the SWOT analysis carried out at PT Arminareka in the marketing strategy for Hajj and Umrah equipment, namely: Utilize PT Arminareka's reputation and experience in the Hajj and Umrah travel industry to develop a comprehensive e-commerce platform, Establish strategic partnerships with travel agents, hotels, and airlines to provide integrated Hajj and Umrah equipment packages, use knowledge and experience in the industry to identify new needs of Hajj and Umrah pilgrims and develop innovative products that meet high quality standards, and improve employee training and development to ensure failed customer service.